ANALISIS KETERAMPILAN METAKOGNISI SISWA MULTIETNIS DI SEKOLAH DASAR MELALUI MODEL PEMBELAJARAN STAD - Muhdar, Rahmat; Sangadji, Harina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This research aims to determine the STAD learning model in empowering students' critical thinking and metacognition skills. Furthermore, this research is aimed at finding out differences in critical thinking skills and metacognition of students of different ethnicities related to the learning model applied. This research is classified as a quasi experiment, carried out in the 2022/2023 academic year in class IV at two schools, SDN 14 and SDN 15, Ternate City, which are classified as multiethnic schools in Ternate City. The variables measured in this research are students' critical thinking skills and metacognition. To test the hypothesis, it was carried out with Anakova in the SPSS 16.0 program. If the probability value is significant, then a further test is carried out with LSD. The results of data analysis show that the learning model has an influence on students' critical thinking skills and metacognition and or it can be said that the PBMP pattern learning model has more potential to empower students' critical thinking skills and metacognition than the conventional model. There are differences in students' critical thinking skills between ethnic groups in classes where the STAD learning model is applied. These differences can be seen in the LSD test results which show that the critical thinking skills of the Ternate ethnic group are not significantly different from those of the Makian ethnic group but are significantly different from those of the Tidore ethnic group. These differences can be concluded that students in each ethnicity have different learning styles.